Effects of periodization in long-term training on the dynamics of changes in punch endurance of a boxer - case study - Hlavacka, P.; Siska, L.; Brodáni, J. (Journal of Combat Sports and Martial Arts, 2017)
Introduction. The aim of this work was to monitor the changes a boxer undergoes in the punch endurance test in relation to special training indicators and subsequently, by means of correlation of the time series, to determine the time shift of the delayed cumulative effect in long-term preparation of boxers. Material and methods. The work has an intraindividual basis. By means of the training logs, we recorded the special training indicators and periodization in the training cycles in accordance with the sporting calendar. The athlete under observation carried out a special punch endurance test on the punch bag in regular 4-week intervals, whose duration was identical with the competitive match. The test was issued by the International Boxing Association (AIBA) in the AIBA Coaches Manual (AIBA Coaches Commission, 2011). When correlating the time series, we used the Spearman`s correlation coefficient. The statistical significance of the relationships has been judged at a 20 % level of significance. Results. The average count in the punch endurance test was RTC1 830,17 ± 75,67 punches and RTC2 867 ± 40,36 punches. Statistically significant correlations with training means of speed endurance (SpdE) 1-2 time shifts (2-4 weeks) and sparring (TT S) 1-3 time shifts (2-6 weeks) have been demonstrated. Conclusions. In terms of the dynamics of changes in special punch endurance, the development copied the systematic periodization of training load, the level improved from accumulation, through the intensification up to the transformation stage, where the best test results were achieved before the top events.